Підвищення ефективності високонавантажених обчислень за допомогою сервісів Azure - Горішня, К. О. (ХНУРЕ, 2025)
The paper examines the use of Microsoft Azure for high-performance computing (HPC) and compares the performance of different virtual machine series (HB, HC, ND). The paper discusses the advantages of cloud solutions over tradІТional ones, including scalabilІТy, cost optimization, and performance. The role of Azure Batch in distributed computing and InfiniBand networks in increasing throughput are analyzed. Based on the research, recommendations are formulated for selecting the optimal Azure services for HPC.
Keywords: ефективність обчислень; високонавантажені обчислення; Azure